Itnab dan Gaya Bahasa AL-Qur'an - Fathurrahman Rauf (Buletin Al-Turas, 2005)
Al-Qur'an has wonderful language and literary style.It contains God's verses and mighty miracles for the prophet Muhammad pbuh. In terms of language and literature, Al- Qur'an is bound with both patterns. Itnab, one of Al-Qur'ans language style, reflects distinguished purpose and function, i.e. to draw the attention of the readers and audience and to affirm its content.